COVID-19 case presented initially with keratoconjunctivitis: A case report. (November 2021) - Alnajjar, Mohammed; Al-Mashdali, Abdulrahman; Nefatti, Nedia
Abstract: Introduction: Ocular complaints are considered non-classical presentations for COVID-19 infection; the initial diagnosis of keratoconjunctivitis is even rarer. Indeed, this puts treating clinicians in danger of getting infected, especially when patients present without the classic respiratory symptoms. Case: Here we report a case of COVID-19 that was initially presented with keratoconjunctivitis with the appearance of respiratory symptoms four days later. The case showed improvement within four days of successful treatment for both covid pneumonia and ocular disease. Discussion: Countable cases reported initial ocular symptoms to co-occur with systemic symptoms or even before. Only two cases reported the diagnosis of keratoconjunctivitis in COVID-19. The two cases differ in the proposed mechanism of developing such disorder. One by direct invasion of the virus, the other one by cytokines-induced epithelial injury. Our case did not show positivity for SARS-CoV 2 in the eye secretion, which aligns with the later proposed mechanism of pathology. Conclusion: It is crucial to report such cases to increase the awareness of atypical presentation for COVID-19 infection. This is too important for two reasons: first, to diagnose the disease itself, and second, to take infection control precautions when treating such cases, with unexpected initial presentation. Highlights: Atypical presentation for COVID-19 infection. COVID-19 may initially present with ocular complains. Countable cases reported initial ocular symptoms to co-occur with systemic symptoms. Infectivity either by direct invasion or cytokines-induced epithelial injury.